Paideia e polyèideia nella cultura ellenistica - Mario Gennari (Firenze University Press, 2013)
The article of Mario Gennari - full professor at the University of Genoa - is a pedagogical analysis of Hellenism. The concept of "polyèideia" is present in this ancient history and it defines the Greek-classical Koinè, when and where Museion, Bibliothéke and Philologoi are the figures of another educational canon. The ancient question of paideia surfaces in this composite scenery, with its load of complexity.